Age-related changes in dentate gyrus cell numbers, neurogenesis, and associations with cognitive impairments in the rhesus monkey - Ngwenya, Laura B.; Heyworth, Nadine C.; Shwe, Yamin; Moore, Tara L.; Rosene, Douglas L. (Frontiers in Systems Neuroscience, 2015)
The generation of new neurons in the adult mammalian brain is well established for the hippocampal dentate gyrus. However, the role of neurogenesis in hippocampal function and cognition, how it changes in aging, and the mechanisms underlying this are yet to be elucidated in the monkey brain. To address this, we investigated adult neurogenesis in the dentate gyrus of 42 rhesus monkeys (39 cognitively tested) ranging in age from young adult to the elderly. We report here that there is an age-related decline in proliferation and a delayed development of adult neuronal phenotype. Additionally, we show that many of the new neurons survive throughout the lifetime of the animal and may contribute to a modest increase in total neuron number in the granule cell layer of the dentate gyrus over the adult life span. Lastly, we find that measures of decreased adult neurogenesis are only modestly predictive of age-related cognitive impairment.